'Englishmen could be proud then, George': echoes of empire in Tinker Tailor Soldier Spy (BBC 1979). Issue 4 (2nd October 2021) - Kiszely, Philip
ABSTRACT: This article considers attitudes towards the British Empire as depicted in the BBC television mini-series Tinker Tailor Soldier Spy (BBC 1979). Broadcast at the end of the 1970s, the decade in which the post-empire era drew to a close, the series shares with its mass audience complex emotions which relate to a pervading sense of national decline. The substance of this exchange – the message of the text and the nature of its reception – indicates a multi-faceted response to the empire grand narrative, especially its final chapter and postscript. How does Tinker Tailor broach the theme of post-empire loss? To what extent does series protagonist George Smiley represent a particular attitude towards empire? In answer to these questions, this article maintains that meditations on the past helped television audiences make sense of their fractured, post-empire present. And that in his quest to unmask a traitor, or Kim Philby-esque 'mole', within MI6, Smiley is as much concerned with conserving aspects of tradition and identity as he is with conflict in purely ideological and geopolitical terms.